Phase transformation induced mechanochromism in a platinum salt: a tale of two polymorphs - Norton, Amie E; Abdolmaleki, Mahmood Karimi; Liang, Jiamin; Sharma, Malvika; Golsby, Robert; Zoller, Ann; Krause, Jeanette A; Connick, William B; Chatterjee, Sayandev (Chemical communications (Cambridge, England), 2020)
Red crystals of [Pt(tpy)Cl]NO3·HNO3 show mechanochromic behaviour turning yellow when pressure is applied. The electronic character and spectroscopic signature of the red and yellow polymorphs change as a result of slipping of the molecular stacking planes in the solid state. The slippage alters the PtPt intermolecular distances from a linear stacked motif with <3.5 Å separations in the red polymorph to a less stacked motif of alternating short intradimer and long interdimer interactions in the yellow polymorph.Red crystals of [Pt(tpy)Cl]NO3·HNO3 show mechanochromic behaviour turning yellow when pressure is applied. The electronic character and spectroscopic signature of the red and yellow polymorphs change as a result of slipping of the molecular stacking planes in the solid state. The slippage alters the PtPt intermolecular distances from a linear stacked motif with <3.5 Å separations in the red polymorph to a less stacked motif of alternating short intradimer and long interdimer interactions in the yellow polymorph.